2015
DOI: 10.5812/hepatmon.15(4)2015.28137
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Salep on Liver

Abstract: Background:Salep is used for various purposes in food industries and traditional medicine. Therefore, evaluation of its effect on the liver seems to be necessary.Objectives:The aim of this study was to assess salep effect on liver.Materials and Methods:In this experimental study, various concentrations of Salep were intraperitoneally administered to five groups of Wistar rats (control, placebo and 20, 40 and 80 mg/kg salep). After one month, liver enzymes and liver tissue were evaluated and compared between di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Significant reduction of increased level of ALT, AST, ALP and bilirubin and marked increased in level of Albumin and Total Protein in Paraquat + Salep treated groups showed that Salep could have protective effect against Paraquat-mediated hepatic injury in dose dependent manner. These results are supported by a previous report which also revealed the protective effect of Salep on liver function[ 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Significant reduction of increased level of ALT, AST, ALP and bilirubin and marked increased in level of Albumin and Total Protein in Paraquat + Salep treated groups showed that Salep could have protective effect against Paraquat-mediated hepatic injury in dose dependent manner. These results are supported by a previous report which also revealed the protective effect of Salep on liver function[ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, generation of nitric oxide and reactive oxygen species like superoxide also play a crucial role in Paraquate - induced hepatotoxicity[ 24 ]. Salep could have protective effect against chemical induced liver injury via reinforcing endogenous antioxidant systems and free radical scavenging[ 12 , 16 ]. As liver is one of the major sites of Paraquat toxicity, this study was done in order to evaluate protective potential of Salep against Paraquat- induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations